Transabdominal amniocentesis in expectant management of preterm premature rupture of membranes: A single center prospective study - Fulová, Veronika; Hostinská, Eliška; Studničková, Martina; Huml, Karel; Zapletalová, Jana; Hálek, Jan; Pilka, Radovan (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2021)
AIMS: The aim of this study was to evaluate the role of IL-6 point-of-care test in amniotic fluid obtained from serial amniocentesis in expectantly managed women with PPROM between 24 and 34 weeks of gestation. METHODS: We conducted a prospective observational cohort study which included 62 pregnant women with PPROM in gestational weeks between 22+0 and 34+0. Women aged >18 years were eligible if they presented with PPROM and a singleton pregnancy. Only women who delivered at >24.0 weeks were included in the study. In all women, the maternal blood sampling and a transabdominal amniocentesis were performed at the time of admission prior to the administration of corticosteroids, antibiotics, or tocolytics, to rule out signs of chorioamnionitis. Maternal temperature, maternal serum C-reactive protein (CRP) and white blood cell (WBC) counts were assayed every subsequent day until delivery. Amniotic fluid was used for the clinical assessment (IL-6 point-of-care test, identification of microorganisms in the amniotic fluid. After one week of expectant management of PPROM, second amniocentesis with amniotic fluid sampling was performed in patients who did not deliver. For all newborns, medical records regarding neonatal morbidity and mortality were reviewed. RESULTS: In total, 62 women aged 19 to 41 years were recruited in the study. The mean gestational age at the time of PPROM was 31+0, the mean gestational age at labor was 32+1, and the median time from PPROM to childbirth was 112 h. IL-6 point-of-care test values above 1,000 pg/mL (positive Il-6 AMC) were found in 12 women (19.4%) with median interval from PPROM to childbirth 56 h (min-max: 6.4-288). IL-6 point-of-care test values below 1,000 pg/mL (negative Il-6 AMC) were found in 51 women (81.0%). The neonatal mortality rate was 1.9% and was associated with prematurity. CONCLUSION: The major clinical finding of our study is that serial transabdominal amniocentesis with Il-6 point-of-care test helps to identify a high inflammatory status in amniotic fluid in women with PPROM. Subsequent expectant management of women with PPROM does not lead to worsening of short-term neonatal outcomes.
Keywords: prospektivní studie; Watchful Waiting; Amniocentesis; Pregnancy; Fetal Membranes, Premature Rupture; lidé; těhotenství; Prospective Studies; ženské pohlaví; Humans; pozorné vyčkávání; Interleukin-6; Female; amniocentéza; předčasný odtok plodové vody; interleukin-6